One EDFA loop in 16 channels spectrum slicing WDM for FTTH access network - Aldouri, Muthana Y.; Syed Alwee Aljunid, Syed Junid, Prof. Dr.; Anuar, Mat Safar; Hilal Adnan, Fadhil; Ahmed, N. (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Link to publisher's homepage at http://ieeexplore.ieee.org/